2009
DOI: 10.1002/hed.21002
|View full text |Cite
|
Sign up to set email alerts
|

Expression modes and clinical manifestations of latent membrane protein 1, Ki‐67, cyclin‐B1, and epidermal growth factor receptor in nonendemic nasopharyngeal carcinoma

Abstract: Our results suggest that the evaluation of EGFR staining intensity in patients with NPC may identify a subgroup of patients with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Further research is needed to evaluate EGFR expression to clinical outcome of NPC. In this large sample study, we found that advancedstage (III-IVa) NPC had a high level expression of EGFR, which was significantly correlated with T stages, clinical stages, local recurrence, and poor prognosis of the patients, and patients with over-expression of EGFR increased risk of locoregional failure and had a reduced survival compared to those patients without, which was in accordance with previous reports [28,29] in NPC and other malignancies [30]. The expression of EGFR intensified in cancer tissues proportional to the increase in tumor extent measured by TNM staging with a statistical significance, indicating that over-expression of EGFR may play some roles not only in NPC pathogenesis but also in NPC progression.…”
Section: Discussionsupporting
confidence: 93%
“…Further research is needed to evaluate EGFR expression to clinical outcome of NPC. In this large sample study, we found that advancedstage (III-IVa) NPC had a high level expression of EGFR, which was significantly correlated with T stages, clinical stages, local recurrence, and poor prognosis of the patients, and patients with over-expression of EGFR increased risk of locoregional failure and had a reduced survival compared to those patients without, which was in accordance with previous reports [28,29] in NPC and other malignancies [30]. The expression of EGFR intensified in cancer tissues proportional to the increase in tumor extent measured by TNM staging with a statistical significance, indicating that over-expression of EGFR may play some roles not only in NPC pathogenesis but also in NPC progression.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we enrolled 15 eligible articles containing survival outcomes [11,[15][16][17][18]22,[24][25][26][27][28][29][30][31][32][33][34][35], among which two studies were written in Chinese [22,33], whereas the others were English articles. These eligible studies were published from 2002 to 2012.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…It has been proved to have significant benefit in clinical treatments for metastatic colorectal cancer, advanced head and neck cancer, and advanced non-small cell lung cancer [17][18][19]. In addition, recent studies have demonstrated that EGFR was overexpressed in .80% of NPC [20][21][22]. Therefore, it is important to investigate the feasibility of applying C225-conjugated USPIO in tumor-targeted imaging.…”
Section: Introductionmentioning
confidence: 99%